PERKEMBANGAN LANDASAN YURIDIS SISTEM PENDIDIKAN NASIONAL UNTUK MEWUJUDKAN SUMBER DAYA MANUSIA YANG HANDAL - ARLIMAN S, LAURENSIUS (Ensiklopedia Education Review, 2019)
The independence of the Indonesian people was proclaimed on the date August 17, 1945. The day after that, on the date August 18, 1945 Preparatory Committee for Indonesian Independence (PPKI) establishes the 1945 Constitution as a State constitution. If you examine the fourth paragraph of the Preamble of the 1945 Constitution, there are express and implied national ideals in the field of education, namely to educate the life of the nation. In connection with this, Article 31 paragraph (3) of the 1945 Constitution mandates that